2020
DOI: 10.1096/fj.202000494rr
|View full text |Cite
|
Sign up to set email alerts
|

Sennoside A prevents liver fibrosis by binding DNMT1 and suppressing DNMT1‐mediated PTEN hypermethylation in HSC activation and proliferation

Abstract: Hepatic stellate cell (HSC) activation is an essential event during liver fibrogenesis. Phosphatase and tension homolog deleted on chromosome 10 (PTEN) is a negative regulator of this process. DNA methyltransferase 1 (DNMT1), which catalyzes DNA methylation and subsequently leads to the transcriptional repression of PTEN, is selectively induced in myofibroblasts from diseased livers. Sennoside A (SA), a major purgative constituent of senna and the Chinese herb rhubarb, is widely used in China and other Asian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 52 publications
(100 reference statements)
0
19
0
Order By: Relevance
“…Treatment with 5'aza-2'-deoxycytidine in activated HSCs model reduced fibrosisassociated gene expression as well as DNMT1 expression while simultaneously enhancing H19 expression and attenuated HSCs activation. Consistently, sennoside A can prevent liver fibrosis by binding DNMT1 and suppress DNMT1-mediated PTEN hypermethylation in HSC activation and proliferation (53).…”
Section: Dna Methylation In Hsc Activationmentioning
confidence: 77%
“…Treatment with 5'aza-2'-deoxycytidine in activated HSCs model reduced fibrosisassociated gene expression as well as DNMT1 expression while simultaneously enhancing H19 expression and attenuated HSCs activation. Consistently, sennoside A can prevent liver fibrosis by binding DNMT1 and suppress DNMT1-mediated PTEN hypermethylation in HSC activation and proliferation (53).…”
Section: Dna Methylation In Hsc Activationmentioning
confidence: 77%
“…In this study, we identified for the first time that the low expression and hypermethylation of ACSM5 gene in tissues and cells of HLF, and overexpression of ACSM5 restrained proliferation, anti-apoptosis, and fibrosis of HLF cells in vitro. DNMT1, a type of DNA methyltransferases (DNMTs), can maintain and catalyze abnormal DNA hypermethylation of CpG islands to cause the loss expression of genes specific, thereby regulating the occurrence and development of various fibrosis-related diseases [ 46 48 ]. Our data demonstrated that the low expression of ACSM5 in HLF cells was negatively regulated by DNMT1, and suppression of DNMT1 restrained the proliferation, anti-apoptosis, and fibrosis of HLF cells in vitro, which can be reversed by silencing ACSM5.…”
Section: Discussionmentioning
confidence: 99%
“…The SA showed mitochondrial protective effect and inhibited hepatic steatosis ( Le et al, 2018 ). Concurrently, SA could also inhibit the proliferation of hepatic stellate cells (HSCs) and suppress the progression of liver fibrosis ( Zhu et al, 2020 ).…”
Section: Pharmacologymentioning
confidence: 99%
“…Interestingly, by using surface plasmonic resonance assay, Zhu et al showed that SA (30 mg/kg in vivo and 10 μM in vitro ) could directly interact with DNMT1 and inhibit DNMT1 in HSCs, resulting in restored PTEN expression and decreased PI3K/Akt activation. Therefore, SA may serve as a promising natural supplement for the treatment of liver fibrosis ( Zhu et al, 2020 ).…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation